AKAR PERMASALAHAN RADIKALISME DAN DAMPAKNYA TERHADAP PERKEMBANGAN ISLAM - Masruraini Masruraini; Muhammad Amri; Indo Santalia (CV. Adiba Aisha Amira, 2022)
Radicalism is a problem that is difficult to solve that will never go away, in fact it may even grow if the government and all of us cannot find the root of the problem and try to find a solution, at least to reduce movements that will actually further damage the order of religious life and the state due to a handful of people. people who have an understanding of radicalism and spread that understanding to the community around them. Radicalism arises as a result of horizontal conflicts that have arisen since the time of the companions, which are more politically nuanced and the unequal understanding of the determination of the position of the caliphate which we know as arbitration. As a developing country, Indonesia must also be aware of this notion of radicalism, especially for children who we call millennials who are still unstable and easily influenced by something new that they may consider to be in accordance with their mindset